Halal Label and Purchase Decisions on Food and Beverage Products: A Case Study in Cipedes Subdistrict Bandung City - Dermawan, Muhammad Jagat; Sudana, Sudana; Samudra, Muhammad Gilang (Jurnal Penelitian Medan Agama, 2024)
This study aims to understand consumer perceptions of halal labels on food and beverage products in Cipedes District, Bandung using qualitative methods. Interviews were conducted with consumers from various backgrounds and analyzed using NVivo software to identify key themes. The results showed that halal labels are considered the main indicator of halalness, quality, and product safety. Words such as halal, belief, religion, safety, and standards dominate the analysis results, confirming the importance of halal labels in building consumer trust. Respondents tend to pay attention to halal labels as the first step before checking other attributes, such as price or nutritional content. Trust in halal certification institutions in the certification process is also a key factor in strengthening consumer perceptions. These findings indicate that halal labels not only function as religious obedience, but also as symbols of quality, safety, and identity. In addition, demographic variables such as age, education, and occupation also influence how consumers interpret halal labels. The results of this study can provide insight for manufacturers to strengthen marketing strategies by emphasizing the credibility of halal certification and its relevance in the social and religious context of consumers.